An analysis on factors influencing oil palm yield productivity of Felcra Berhad: perspective of estate management / Fazrul Naim Abdul Wahab - Abdul Wahab, Fazrul Naim (Faculty of Plantation and Agrotechnology, 2018)
FELCRA manage quite a number of smallholders’ estate and are a vital part of the Malaysian palm oil supply chain, but they often produce fewer yields than big firms. This is partly due to the differences in management styles of the estate. Managing the estate in accordance with the correct nutrient requirement and condition of the plant will improve the production of oil palm fresh fruit bunches (FFB). Hence, this study are being carried out to analyse the factors influencing oil palm yield productivity by considering 3 criteria which is pest and disease management, fertilizer management and field’s maintenance. A total of 12 oil palm estates under the FELCRA scheme in Melaka are being studied by analysing data taken from set of questionnaires given to the person in charge of the estate. Results have shown that only one variable, fertilizer management has significant relationship with the FFB yield per hectare obtained. Only when factors determining oil palm productivity are understood, the desired production of fresh fruit bunches can be achieved.